ChemInform Abstract: Crystal Structure of CdSO4(H2O): A Redetermination. Issue 1 (17th December 2015) - Theppitak, Chatphorn; Chainok, Kittipong
Abstract: Crystals CdSO4 (H2 O) are hydrothermally grown from an aqueous solution of equimolar amounts of CdSO4 ·8/3H2 O and 3, 6‐di‐2‐pyridyl‐1, 2, 4, 5‐tetrazine (autoclave, 356 K, 5 d).